El problema existencial en los personajes Martín y Alejandra de “Sobre Héroes y Tumbas” de Ernesto Sábato - Carbajal Cueva, Iris Nataly (2017)
Literature is an artistic expression that is born from the interior of man. It is an escape and a form of catharsis in front of the existential condition of the human being. This is very reflected in the work On Heroes and Tombs of Ernesto Sábato, which we have investigated._x000D_ The main characters of this novel, Martin and Alejandra, are beings exposed to the influence of existentialism that preaches Jean Paul Sartre. The main topics that are developed through the actions of these two characters are: loneliness and anguish. Therefore, our study begins with the concept of existentialism, exponents, types, topics (solitude and anguish), to, in the theoretical framework, approach the actantial theory proposed by Julius Greimas. After presenting these aspects, we discuss how existentialism develops in Latin America and its influence on Ernesto Sábato._x000D_ Finally, in the discussion of results, we analyze existential topics such as loneliness and anguish, in the characters Martín and Alejandra and their relation to the actantial scheme of Julius Greimas: subject-object.